WavLM: Large-Scale Self-Supervised Pre-Training for Full Stack Speech Processing - Chen, Sanyuan; Wang, Chengyi; Chen, Zhengyang; Wu, Yu; Liu, Shujie; Chen, Zhuo; Li, Jinyu; Kanda, Naoyuki; Yoshioka, Takuya; Xiao, Xiong; Wu, Jian; Zhou, Long; et al. (IEEE Journal of Selected Topics in Signal Processing, 2022)
Self-supervised learning (SSL) achieves great success in speech recognition, while limited exploration has been attempted for other speech processing tasks. As speech signal contains multi-faceted information including speaker identity, paralinguistics, spoken content, etc., learning universal representations for all speech tasks is challenging. To tackle the problem, we propose a new pre-trained model, WavLM, to solve full-stack downstream speech tasks. WavLM jointly learns masked speech prediction and denoising in pre-training. By this means, WavLM does not only keep the speech content modeling capability by the masked speech prediction, but also improves the potential to non-ASR tasks by the speech denoising. In addition, WavLM employs gated relative position bias for the Transformer structure to better capture sequence ordering of input speech and scale up the training dataset from 60k hours to 94k hours. WavLM Large achieves state-of-the-art performance on the SUPERB benchmark and brings significant improvements for various speech processing tasks on their representative benchmarks. The code and pre-trained models are available at this URL.